Susumaton oral narratives of Leyte - Alunan, Merlie M. (Quezon City Ateneo de Manila University Press, 2016)
"From the Waray word "sumat" for "to tell," the susumaton are oral narratives told by the paragsumat, or storykeepers, either informally during social gatherings or in a more formal fashion in the case of tales of a more formal provenance such as a folklore. The stories are rooted in the country's rich and continuous oral traditions, a treasure trove that includes epics, proverbs, riddles, and songs, among others, all of which predate the arrival of the Spanish in the 16th century. Gathered in Susumaton are 98 of these narratives collected from seven towns in Leyte: Dulag, La Paz, Tolosa, Tanauan, Palo, Barugo, and Carigara. In the book, they are presented as they were told, enabling the reader to echo the storyteller's voice as he reads. English translations are supplied, and an informative introduction by Alunan provides context."--Provided by the publisher.
An mga umurukoy ha Bough Building=The dwarf dwellers of Bough Building Amador Profetana -- Mga umurukoy ha Sabang=Invisible residents of Sabang Florencio Marpa -- Bubon=The dwell Diana Quiña -- Makaharadlok nga Katulangan=The perils of Katulangan Arcadia Acebo -- An lungib ha Bangon=The mysterious cave of Bangon Manuel Ipil -- Urusahon nga dalan tikadto ha Barugo=The mysterious road to Barugo Nena Oyzon -- Dida ha Salangi=A place called Salangi Lucila Lurica -- Hi Domingo Oriogue= A man named Domingo Oriogue Jose Negado, Panfilo Insigne -- An Boholano ha Canumantag=The Boholano who staryed to Canumantag -- An tulay ha Canumantag=The mysterious Canumantag Bridge -- Kardagaw=A man named Kardagaw Eduardo Oyzon -- Sangkay nga engkantohanon=My engkanto friends Flora Buena -- Hi Apoy Merin ug an tawo nga sisihon=Apoy Merin and the barnacled man Fe Apostol Silay -- Kalaghongan=Kalaghongan Isabel Arandia -- Mga higante ha Tolosa=The giants of Tolosa Mike kahano -- An anakan nga naengkanto=A young mother wooed by a fairy man Concepcion Serdeña -- Hi Gimay=A woman named Gimay Matile Marpa -- Higante nga bisita=Visit from a giant Corazon Acebo -- Aswang=Witch Pomposa Musca -- Hi Pedring paradalos=Pedring the weeder Fe Apostol Silay -- Bata nga tambalan=The child healer Corazon Colasito -- An akon Tatay nga tambalan=My father, the medicine man Concepcion Serdeña -- Sangkay nga nalupad=Friend with a flier Consolacion Acebo -- Hi Bata Islaw ngan iya mahika blanka=Uncle Islaw and his white magic Jorge Abejo -- Apoy Ombing=Apoy Ombing Catalina Arminal -- Hi Ombing han Carigara=Ombing of Carigara Eufracio Gavero -- Ginbuyong hi Mana Bebeng='Nay Bebeng loses her way home Fe Apostol Silay -- Mga urusahon: balod, ayam, ug uban pa=Strange events: big waves, mysterious dog, etc. Filomena Cinco -- An kan Nanay intra nga aghoy=Nanay's fairy suitor Flora Buena -- An milagrosa nga birhen=The miraculous virgin Rosendo Musca -- Tamsi nga nagpahupay han balod=The bird that soothed the wave Consolacion Merida -- An milagroso nga kalendaryo=The miraculous calendar image Jovita Sencio -- Nagmumulto nga parupamatbat=Ghost of a prayer leader Salud Mendoza -- An kapre ngan an bata ha kamiyapian=The kapre and the babe in the woods Fe Apostol Silay -- Peligroso nga pan-ngahoy=a perilous wood-gathering adventure Corazon Acebo -- An mangirhat nga kamatayon ni Nanay=My mother's strange horrying death Virginia Cañeda -- An paraalog ha langwad=The boy who fetched water in a basket Concordia Oyzon Botelya han asyete=Bottle of oil Corazon Acebo -- Urusahon nga karabaw=The strange carabao Fe Apostol Silay -- An bias ni Apoy=Grandma's jar Consolacion Acebo -- An Ginbakasyonan=Ginbakasyonan Teodulo Tuando -- An Bukid Gin-ankan ha Carigara=Birthing Hill of Carigara Reynaldo Naagas Sr. -- An naghahablon nga nahimong bato=The woman weaver who turned into stone Maria Maceda-Collado -- Moros=Moros Filomena Cinco -- An tinikangan han Tanauan=The beginning of Tanauan -- Baluarte=Baluarte Mike Kahano -- Panaghon han Hapon=The Japanese times Pablo Pesado -- Pan-looting=Looting -- Pag-abot han Amerikano=When the Americans came -- An buayahon=Crocodile lover Victorio Piñero -- An babayi nga anay tinamay=The woman despised Segundo Quilaneta -- Una nga kalipay, urhi nga pagbasol=Pleasure comes first, regret follows Severino Caindoy -- Bukaw harakpaw!=Bukaw harakpaw! Jovita Secio -- Ha baka han bako= In the mouth of a frog Froilan Fundavela -- An kamanokan ni Man'Tonying Pudol=Man'Tonying Pudol's chickens -- Ardi=Ardi Mike Pesado, Pablo Pesado -- Obispo Odon=Bishop Odon Victorio Piñero -- Kun kay ano nga karabaw nabulig ha tawo=Why the carabao is helpful to humankind Jose Pedrosa Durango -- An uding ngan leon=The cat and the lion Maria Maceda-Collado -- An mananggiti ngan an bila=The mananggiti and the crocodile Norberto Busa -- Hi Hangagay ngan hi Amoay=The turtle and the monkey Norberto Busa -- Vicente Wati=Vicente , the worm Severino Caindoy -- Hi Dulay=About Dulay Ciriaco Agner -- Don Juan Teñeso=Don Juan Teñeso, the beggar prince Severino Caindoy -- Kaagi ni Don Juan Teñeso=The saga of Don Juan Teñeso Segundo Quilaneta -- Hi Pikas=Mr. One Half Leoncio Cabazares -- Blanca Nieves=Blanca Nieves Anacleto Calaque -- Regalo han alimango=The crab's bequest Luciano Cabazares -- Hi Gregorio Magno ngan hi Rosaura=Gregorio Magno and Rosaura Maria Maceda-Collado -- Bukad, pisi, ngan dagom=Flower, rope, and needle Eugenia Agullo -- An tika=The witch wife Sotera Espino -- An mga uyagan ni Intoy=Intoy's playthings Luciano Cabazares -- Portuna ni Pedro=Pedro's fortune Leoncio Cabazares -- Hi Jaime ngan an iya bugto nga kabayo nga nalupad=Jaime and his brother, the flying horse Anacleto Calaque -- Sandangaw=Mr. One Handspan Alberto Suarez -- An gugma ni Juan Bahag=The love of Juan Bahag Antonio Oyzon -- An kinabuhi ni Pedro Villafranca Jr.=The adventures of Pedro Villafranca Jr. Anacleto Calaque -- An nag-aaringaring=Courtship Maria Maceda-Collado -- Kun mapatay ako=If I am dead Seferina Nario -- An tuba=Tuba Damian Maceda -- Burod hi Padre=Padre is pregnant Leoncio Cabazares -- An kandidato nga waray data=The good-for-nothing candidate Anacleto Calaque -- An danggab=The witch -- An pikoy ug an padi=Pikoy and the Padre Severino Caindoy -- An pikoy nga nagpaka-Kristo=The parrot who pretended to be Christ Segundo Quilaneta.
Includes bibliographical references.
In English; with original in Waray.
Keywords: Folklore -- Philippines -- Leyte Island; Tales -- Philippines -- Leyte Island; Legends -- Philippines -- Leyte Island